Myeloid cells as potential targets for immunotherapy in pediatric gliomas - Frederico, Stephen C.; Sharma, Nikhil; Darling, Corbin; Taori, Suchet; Dubinsky, Alexandra C.; Zhang, Xiaoran; Raphael, Itay; Kohanbash, Gary (Frontiers in Pediatrics, 2024)
Pediatric high-grade glioma (pHGG) including pediatric glioblastoma (pGBM) are highly aggressive pediatric central nervous system (CNS) malignancies. pGBM comprises approximately 3% of all pediatric CNS malignancies and has a 5-year survival rate of approximately 20%. Surgical resection and chemoradiation are often the standard of care for pGBM and pHGG, however, even with these interventions, survival for children diagnosed with pGBM and pHGG remains poor. Due to shortcomings associated with the standard of care, many efforts have been made to create novel immunotherapeutic approaches targeted to these malignancies. These efforts include the use of vaccines, cell-based therapies, and immune-checkpoint inhibitors. However, it is believed that in many pediatric glioma patients an immunosuppressive tumor microenvironment (TME) possess barriers that limit the efficacy of immune-based therapies. One of these barriers includes the presence of immunosuppressive myeloid cells. In this review we will discuss the various types of myeloid cells present in the glioma TME, including macrophages and microglia, myeloid-derived suppressor cells, and dendritic cells, as well as the specific mechanisms these cells can employ to enable immunosuppression. Finally, we will highlight therapeutic strategies targeted to these cells that are aimed at impeding myeloid-cell derived immunosuppression.